The Effect Of Leadership Style, Work Motivation, And Work Stress On Employee Performance At PT. Bank Rakyat Indonesia, Bengkulu Branch Office - Dwioktaputri, Widia; Soleh, Ahmad; Febliansa, Muhammad Rahman (UNIVED Press, 2026)
This study aims to analyze the influence of leadership style, work motivation, and work stress on employee performance at PT Bank Rakyat Indonesia (Persero) Tbk, Bengkulu Branch Office. The research was conducted to understand how managerial behavior, psychological factors, and workplace conditions collectively affect the overall performance of employees in the banking sector.The research employs a quantitative approach using primary data collected through questionnaires distributed to employees of PT Bank Rakyat Indonesia Bengkulu Branch. The data were analyzed using SmartPLS 4.0 to test the measurement model (outer model) and the structural model (inner model).The results reveal that leadership style has a positive and significant effect on employee performance, indicating that effective leadership can enhance employees’ enthusiasm, responsibility, and productivity. Work motivation also has a positive and significant effect, suggesting that motivated employees tend to perform better and show higher commitment to their tasks. Meanwhile, work stress shows a positive but not significant effect on employee performance, meaning that the level of stress experienced by employees is still within manageable limits and does not significantly hinder performance outcomes.Overall, the findings highlight that leadership and motivation are the key drivers of employee performance, while stress management remains an important aspect to maintain a healthy and productive work environment. The implications of this study suggest that PT Bank Rakyat Indonesia should strengthen leadership quality, improve motivation systems, and manage work-related stress to sustain and enhance employee performance.